Barriers and enablers to implementing clinical practice guidelines in primary care: an overview of systematic reviews - Tao Wang; Xian-Liang Liu; Jing-Yu (Benjamin) Tan; Isabella Zhao (BMJ Open)
Objectives To identify the barriers and enablers to implementing clinical practice guidelines (CPGs) recommendations in primary care and to provide recommendations that could facilitate the uptake of CPGs recommendations.Design An overview of systematic reviews.Data sources Nine electronic databases (PubMed, Cochrane Library, CINAHL, MEDLINE, PsycINFO, Web of Science, Journals @Ovid Full Text, EMBase, JBI) and three online data sources for guidelines (Turning Research Into Practice, the National Guideline Clearinghouse and the National Institute for Health and Care Excellence) were searched until May 2021.Eligibility criteria Systematic reviews, meta-analyses or other types of systematic synthesis of quantitative, qualitative or mixed-methods studies on the topic of barriers and/or enablers for CPGs implementation in primary care were included.Data extraction and synthesis Two authors independently screened the studies and extracted the data using a predesigned data extraction form. The methodological quality of the included studies was appraised by using the JBI Critical Appraisal Checklist for Systematic Reviews and Research Syntheses. Content analysis was used to synthesise the data.Results Twelve systematic reviews were included. The methodological quality of the included reviews was generally robust. Six categories of barriers and enablers were identified, which include (1) political, social and culture factors, (2) institutional environment and resources factors, (3) guideline itself related factors, (4) healthcare provider-related factors, (5) patient-related factors and (6) behavioural regulation-related factors. The most commonly reported barriers within the above-mentioned categories were suboptimal healthcare networks and interprofessional communication pathways, time constraints, poor applicability of CPGs in real-world practice, lack of knowledge and skills, poor motivations and adherence, and inadequate reinforcement (eg, remuneration). Presence of technical support (‘institutional environment and resources factors’), and timely education and training for both primary care providers (PCPs) (‘healthcare provider-related factors’) and patients (‘patient-related factors’) were the frequently reported enablers.Conclusion Policy-driven strategies should be developed to motivate different levels of implementation activities, which include optimising resources allocations, promoting integrated care models, establishing well-coordinated multidisciplinary networks, increasing technical support, encouraging PCPs and patients’ engagement in guideline development, standardising the reporting of guidelines, increasing education and training, and stimulating PCPs and patients’ motivations. All the activities should be conducted by fully considering the social, cultural and community contexts to ensure the success and sustainability of CPGs implementation.